Low‐carbohydrate diet score and risk of bladder cancer: Findings from a prospective cohort study - Yen Thi‐Hai Pham; Renwei Wang; Jian‐Min Yuan; Hung N. Luu (BJUI Compass)
Abstract Objective Low carbohydrate diet (LCD), a summary score considering sources of all macronutrients in a dietary pattern, is defined by lower intakes of carbohydrates and higher intakes of proteins and fats. Research on the role of LCD and risk of bladder cancer is scare. We, therefore, prospectively examined the association between LCS scores and bladder cancer risk. Patients and Methods We used data from the Singapore Chinese Health Study, a prospective cohort study of 63 275 participants aged 45–74 living in Singapore who were recruited during 1993–1998 period. LCD scores were derived from the semi‐quantitative food frequency questionnaire at baseline. Bladder cancer cases were identified through record linkage with the Singapore cancer registry. Cox proportional hazard regression method was used to calculate hazard ratios (HRs) and 95% confidence intervals (CIs) for bladder cancer in relation with LCD scores. Results After 17.6 years of follow‐up with 819 573 person‐years, 250 participants developed bladder cancer. We found a statistically significant, positive association for bladder cancer risk with increasing level of animal‐based LCD (HRper‐SD increment = 1.16, 95% CI: 1.02–1.32; Ptrend = 0.01), but a null association with an increased level of plant‐based LCD (HRper‐SD increment = 1.08, 95% CI: 0.91–1.28, Ptrend = 0.78). Conclusion In summary, we showed that an LCD diet with fat and protein from animal‐based food was associated with increased risk while an LCD diet with fat and protein derived mainly from plant‐based food was not associated with bladder cancer risk. Our findings have implications for diet modifications in the prevention and control program of bladder cancer.